Economics, Politics, and Ethics of Primary Commodity Development : How Can Poor Countries in Africa Benefit the Most? - Lele, Uma (IMF Working Papers; Working Paper, 1994)
The critical role of agricultural commodities in the growth of low-income countries is examined. A combination of factors has resulted in declining agricultural prices, necessitating further increasing volumes by developing countries to maintain export earnings. But low growth in factor productivity in Africa compared to competitors caused declining export shares in African countries. A broad-based smallholder strategy based on producing commodities in which a country enjoys comparative advantage needs to be supported by productivity enhancing innovations in food and export commodities, a stable price environment, availability of infrastructure and access to credit. Such an environment requires partnership between government and private agents.